Praktik Unpaid Internship Dalam Perkembangan Regulasi Ketenagakerjaan Indonesia (Studi Kasus Campuspedia) - Suraya Imtiyaaz; Wahyu Donri (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
The trend of unpaid apprenticeship programs is increasingly being found. Due to the increasingly high competition, many are still interested in joining the apprenticeship program without pay, with the lure of work experience for the next career step. The growing interest in unpaid internships is also supported by the company's strategy to reduce expenses and the high desire of prospective interns to gain knowledge in the field of work. Companies often use this condition to obtain workers who are not bound by a minimum wage. If it continues to happen, the purpose of apprenticeship, which was initially skills training, becomes exploitation of workers. The purpose of writing is to analyze unpaid apprenticeships in increasing the integrity of the workforce in Indonesia, how the Indonesian workforce views the practice of unpaid apprenticeships and the government's role as a labour regulator in Indonesia. This analytical descriptive study utilizes a normative legal research typology, a normative juridical approach and is analyzed through a qualitative approach. The study results show that the apprenticeship programs' regulations still need to be specific, especially regarding the wage rights of apprentice workers. The government, as a regulator, should understand the high interest in apprenticeship programs, so clear legal protection is needed for apprentices. The outcome of this paper will be the awareness of the lack of strict regulations protecting the rights of apprentices based on one of the cases, namely the Campuspedia apprenticeship, to continue to be critically studied.